Benarkah Kesehatan Mental Mahasiswa/i Bermasalah Akibat Tugas Perkuliahan yang banyak ? Study Literatur Penyebab Masalah Kesehatan Mental - AI AULIYA; Teofilus Ardian Hopeman (Jurnal BELAINDIKA (Pembelajaran dan Inovasi Pendidikan), 2024)
One of the factors that determine whether teenagers are more vulnerable to mental disorders is that teenagers tend to have explosive emotional outbursts. One of the causes of psychological disturbance in this group of students is excessive workload. This research used the literature review or literature study method. Through this literature review, the author will find various data and information that can be used through various journals and books as answers to the problems that the author is studying. This research aims to find out how to prevent mental health problems experienced by students. The results of this research show that mental health refers to an individual's condition that facilitates progress in all dimensions of development, such as physical, intelligence, and emotional, towards their best potential which is in line with the development of others. Aspects of mental health also include efforts to manage stress, difficulties in adaptation, interactions with other people, and decision-making processes. Students feel that the final assignment is quite a heavy burden. Anxiety is a personal sensation related to feelings of tension, restlessness, and worry associated with increased nervous system activity. Students are carrying out their final assignments which are considered to be a difficult task that can cause anxiety. The impact felt by students will be sleep disturbances, lack of rest time, and unhealthy eating patterns. One of the first steps is for students to have a good understanding of their body condition, including physical and mental. students can relax for their body and mind.